Sertraline and Alprazolam in the Treatment of Panic Disorder - Saida Fišeković; Svjetlana Loga-Zec (Biomolecules & Biomedicine, 2005)
A compared, 12 week, placebo controlled study, with fixed dose, outpatient study of patients diagnosed with panic disorder with and without agoraphobia according to ICD-10, was conducted to evaluate the efficacy and safety of sertraline and alprazolam. The study included 40 patients, divided in two groups. We evaluated number of ICD-10-defined panic attacks, agoraphobia and anticipatory anxiety. All patients were aged 18 year and older and were randomized to either sertraline or alprazolam. Sertraline applied in fixed doses of 20 mg/day and alprazolam in doses 1-1,5 mg/day significantly reduced the frequency of panic attacks in panic disorder patients, reduced symptoms of agoraphobia and anticipatory anxiety